The Perspectives of Young Women in Rural Western Kenya on Unconditional Cash Transfers. Issue 1 (March 2016) - Junior, Jean A.; Katz, Arlene M.; Ahn, Roy
Abstract: Unconditional cash transfers (UCTs) provide money to eligible individuals, without dictating how they spend the money or tasks they must do to receive it. This study explored how UCTs affected the lives of young, impoverished women in rural western Kenya. Qualitative methods were used, including in‐depth interviews with 30 women: 10 receiving $1, 000, 10 receiving $500, and 10 not receiving a UCT. UCTs were positively viewed by interviewees, and had nuanced and varied effects on aspirations, money management, relationships, and subjective well‐being in social context. The perspectives of interviewees offer programmatic suggestions and question major assumptions concerning UCTs. The perspectives of interviewees offer programmatic suggestions and question major assumptions concerning UCTs. This qualitative study augments the primarily quantitative research on UCTs that has been done to date.